Handbook of Legal Reasoning and Argumentation (Springer Netherlands, 2018)
This handbook addresses legal reasoning and argumentation from a logical, philosophical and legal perspective. The main forms of legal reasoning and argumentation are covered in an exhaustive and critical fashion, and are analysed in connection with more general types (and problems) of reasoning. Accordingly, the subject matter of the handbook divides in three parts. The first one introduces and discusses the basic concepts of practical reasoning. The second one discusses the general structures and procedures of reasoning and argumentation that are relevant to legal discourse. The third one looks at their instantiations and developments of these aspects of argumentation as they are put to work in the law, in different areas and applications of legal reasoning. .